Variability in Antinuclear Antibody Testing to Assess Patient Eligibility for Clinical Trials of Novel Treatments for Systemic Lupus Erythematosus. Issue 9 (5th August 2019) - Pisetsky, David S.; Thompson, Dana Kathryn; Wajdula, Joseph; Diehl, Annette; Sridharan, Sudhakar
Abstract : Objective: In the development of novel therapies for systemic lupus erythematosus, antinuclear antibody (ANA) positivity represents a criterion for trial eligibility. Since as many as 30% of patients enrolled in trials have been ANA negative, we evaluated the performance characteristics of immunofluorescence assays (IFAs) for ANA determinations for screening. Methods: This study used 5 commercially available IFAs to assess the ANA status of 181 patients enrolled in a phase II clinical trial for an anti–interleukin‐6 antibody. Enrollment included a detailed review of medical records to verify a historical ANA value. IFA results were related to various clinical and serologic features at enrollment. Results: While the frequency of ANA negativity assessed by the central laboratory was 23.8% in a cohort of 181 patients, the evaluated IFA kits demonstrated frequencies of negativity from 0.6 to 27.6%. With 2 IFA kits showing a significant frequency of ANA negativity, positive and negative samples differed in levels of anti–double‐stranded DNA, C3, and presence of other ANAs as well as the frequency of high interferon (IFN) expression. Conclusion: These findings indicate that, when used for screening, IFAs can vary because of performance characteristics of kits and thus can affect determination of trial eligibility. With kits producing a significant frequency of ANA negativity, ANA status can be associated with other serologic measures as well as the presence of the IFN signature, potentially affecting responsiveness to a trial agent.